A Study on the Promotion of P3A Participation In Operation and Maintenance of The irrigation Network in Regency of Tanah Datar - (NIM : 95005322), YULIADRA
In attempt to investigate those factors that have influence on the promotion of P3A participation in the operation and maintenance of irrigation network in Regency of Tanah Datar, managed by using nagari irrigation system, a case study was conducted on the best P3A at West Sumatra Province level, that from 2004 to 2006 came from Regency of Tanah Datar. This research used quantitative and qualitative analysis (path analysis), with independent variable X1 (organization), independent variable X2 (finance), independent variable X3 (operation), independent variable X4 (maintenance), and dependent variable VI (cultural aspect). Data from questionnaire results was used as ordinal data and transformed into interval data by MSI method, while by using SPSS.13 it was obtained correlation value of XI and Y1 = 0,76 (very strong), X2 and Y1 = 0.75 (strong), X3 and VI = 0.75 (strong), X4 and Y1 = 0.59 (strong), and regression value of Y1 = 0.295 X1+0.259 X2+0.259 X3+0.089 X4+3.448, meaning that all independent variables have influence and are correlated with dependent variable. A practice of P3A to hold a traditional spiritual ceremony after each harvest was very effective in collecting retribution, so the collected retributions increased from <70% to >95%, and Real Needs Rate of the Irrigation Network's Operation and Maintenance could be fulfilled. Cultural-based P3A guidance by Nagari Rule led irrigation management into nagari irrigation system by prioritizing togetherness, collaboration, and enforcement of nagari customary rules, leading to the increase of P3A participation in the operation and maintenance of irrigation network.